STUDY OF REFRIGERATION SYSTEM AND NUMERICAL SIMULATION OF AIR DISTRIBUTION FOR FISH COLD STORAGE. - LUNTUNGAN (NIM : 231 04 018); Pembimbing : Dr. Ir. Prihadi Setyo Darmanto, HENGKY
Cold storage is a room for preservation, refrigeration and freezing agricultural, farming and fishery product with purpose to pursue degradation of product quality before distributed to market. Cold storage in this research is focused for fish cold storage with storage temperature around - 29 oC to - 23 oC and relative humidity 90 Ã‚Â± 10%. Design of cooling system for cold storage is including to design for blast freezer and cold storage itself. Design of refrigeration system include the calculation of cooling load for blast freezer and cold storage, and the calculation of machine capacities and choosing the machine for the blast freezer and cold storage. Calculation of air distribution is done for cold storage that designed with using air duct for its refrigeration system. The result of calculation cooling load for blast freezer and of cold storage respectively is 77,788 kW and 28,142 kW. The system for the refrigeration is standard vapor compression system by using R22 as refrigerant. After that, the calculation for estimating operation cost of blast freezer and cold storage and got the lowest operating cost is around Rp 24,4 million per month. Numerical simulation of this research is used for simulate the temperature and relative humidity distribution of cold storage by 2 (two) alternative air distribution system. The result of numerical simulation by using software Fluent 6.1 showing that uniform temperature distribution with average temperature around - 29 oC for both selected alternative but only the second alternative which assign the value relative humidity with uniform distribution of relative humidity around 60% (for empty cold storage). After that numerical simulation the second alterative with addition vapor injection got the relative humidity around 80%. Choosing the refrigerant is to get expected high energy conversion efficiency and economic cost. The selected refrigerant is R22, R134a, R404a, R407c, R507a and of R717. The research result got R22 is the most efficient refrigerant. The research result show that R152a is the best refrigerant for replacing R22.